The genealogy of integrationism: Ideational foundations of the politics of immigrant integration - Dodevska, Iva (Frontiers in Political Science, 2023)
This article traces the idea of (“immigrant”) “integration” from its roots in classical political philosophy and the birth of the modern nation-state, to its current relevance in the European political agenda and, relatedly, its centrality in the newly consolidated field of Migration Studies. I examine the ontological (i.e., philosophical and sociological) and political rationales behind the idea that migrants need to “integrate into society”, and the different varieties of political solutions that are offered in this sense. The paper asks: How did the migrant come at the center of the idea of an integrated society? And how did integrationism become consolidated as the hegemonic idea of governing diverse societies in post-migration contexts in Europe? Employing an extensive list of secondary literature, documentary data, policy analysis of the EU-level Framework on migrant integration, and discourse analysis of integration-related research publications, I attempt a genealogy of the idea of “integration” as it traveled across the North Atlantic West and between academia and government. The paper shows how the production of the subject of integration—the misfit “immigrant” figure—is historically marked by a consensus across the learned and the governing elites that identifies the preservation of a homogenous national social order as a societal goal. I argue that the scientification of integration governance via the “evidence-based policy” paradigm (most notably promoted by EU institutions) normalizes, naturalizes and aims to depoliticize the otherwise highly normative and contested question of migrant integration.